GENERALIZED PERIODONTITIS AND RHEUMATOID ARTHRITIS: IMUNOLOGICAL ASPECTS OF MUTUAL AGGRAVATION - S. I. Smiyan; I. P. Mazur; I. I. Bilozetskyi (Zaporozhye State Medical University, 2014)
Aim. The combination of rheumatoid arthritis and periodontitis may have an adverse prognostic significance for both diseases. Methods and results. In order to study the relationships between generalized periodontitis course and tumor necrosis factor alpha (TNF-α) level 60 patients with rheumatoid arthritis were examined. Conclusion. It was established that markers of activity and aggression of rheumatoid arthritis, such as the presence of rheumatoid factor, antibodies to cyclic citrullinated peptide and increased level of TNF-α, play a key role in the progression of periodontitis.